SiGe HBT low noise amplifiers for ultra-wideband systems - Popov, V. P.; Sidorenko, V. P. (Technology and design in electronic equipment, 2013)
This paper presents the principles of design of integrated circuits low-noise amplifiers (LNA) based on silicon-germanium heterojunction bipolar transistors (SiGe HBT) for ultra-wideband (UWB) systems. UWB systems range 0,5–10,6 GHz are used in communications, radars of medical applications and safety systems. The proposed UWB LNA implemented by inductorless or minimum number of inductors schemes. In this paper researched and designed two variants of UWB LNA 0,5–11 GHz frequency range.